Revaluation of the COVID-19 pandemic impact on the epidemiology of syphilis in Brazil - Marques, Nelson Pereira; Marques, Nádia Carolina Teixera; Silveira, Denise Maria; Martelli, Daniella Reis Barbosa; Oliveira, Eduardo Araújo; Martelli-Junior, Hercílio (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Due to the coronavirus 2019 disease (COVID-19) pandemic, health systems worldwide have suffered interferences, with the interruption of sexual health clinics, limitation of ambulatory consults, prevention, diagnosis, and treatment of several diseases, especially syphilis, altering their epidemiology. Objective: To investigate the impact of the pandemic on syphilis diagnosis in Brazil, the main goal of this study was to update and reevaluate data from the Brazilian Unified Health System on the number of syphilis cases reported in all five Brazilian geographic regions and verify the response of the Brazilian health care to the COVID-19 pandemic. Methods: The data were retrieved from the National Disease Notification System and the Department of Chronic Conditions Diseases and Sexually Transmitted Infections and represent syphilis diagnosis in Brazil, from March to December 2017 to 2019, 2020, and 2021. Results: The increase in the number of syphilis cases was minor compared to 2020, keeping the Southeast region as the most impacted (+146.1%) and an increase of 22,633 cases throughout Brazil (+54.3%). Conclusion: Syphilis disease control measures were ineffective in 2021 as the drop in the number of cases was irrelevant compared to the years before the pandemic. The association between the increase in syphilis cases in Brazil and the COVID-19 pandemic should be further investigated to assist in decision-making processes and in the programming of health actions in addition to finding measures to raise the control of this disease.